Antiplasmodial effect of the venom of Crotalus durissus cumanensis, crotoxin complex and Crotoxin B (2012)
The antiplasmodial activity of phospholipases A2 (PLA2) isolated from different animals has been studied. We explored the in vitro anti Plasmodium falciparum effect of a fraction containing crotoxin, Crotoxin B and whole venom of the rattlesnake Crotalus durissus cumanensis. Fraction II (crotoxin complex) was obtained by size exclusion chromatography, whereas Crotoxin B was purified by RP-HPLC. The whole venom is active against the parasite at concentrations of 0.17±0.03µg/ml, fraction II at 0.76±0.17µg/ml and Crotoxin B at 0.6±0.04µg/ml. Differences were observed in the cytotoxic activity against peripheral mononuclear cells, with Crotoxin B exhibiting the highest cytotoxicity. The concentration of Crotoxin B required to exert cytotoxic activity was higher than that required to exert antiplasmodial activity. Lethality in mice confirmed the higher toxicity and neurotoxicity of whole venom and fraction II, whereas Crotoxin B was not lethal at the doses tested. These results suggest the potential of Crotoxin B as a lead compound for antimalarial activity. © 2012 Elsevier B.V..